2008
DOI: 10.1002/iub.47
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: One molecule, many targets

Abstract: SummaryResveratrol is one of the numerous polyphenolic compounds found in several vegetal sources. In recent years, the interest in this molecule has increased exponentially following the major findings that resveratrol (i) is shown to be chemopreventive in some cancer models, (ii) is cardioprotective, and (iii) has positive effects on several aspects of metabolism, leading to increased lifespan in all the metazoan models tested thus far, including small mammals. Such remarkable properties have elicited a vast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
233
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(243 citation statements)
references
References 81 publications
2
233
0
8
Order By: Relevance
“…Resveratrol has been shown to increase lifespan and promote health span in model organisms ranging from yeast, worms, flies, and mice (Allard et al 2009;Pirola and Frojdo 2008). However, the prolongevity effect of resveratrol and its underlying mechanisms have been challenged by studies from several labs and remain controversial (Bass et al 2007b;Kaeberlein et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resveratrol has been shown to increase lifespan and promote health span in model organisms ranging from yeast, worms, flies, and mice (Allard et al 2009;Pirola and Frojdo 2008). However, the prolongevity effect of resveratrol and its underlying mechanisms have been challenged by studies from several labs and remain controversial (Bass et al 2007b;Kaeberlein et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuins are generally thought to mediate lifespan by DR, although this view along with the prolongevity effect of resveratrol has been challenged (Baur 2010). A number of follow-up studies have revealed that resveratrol modulates activities of many targets besides sirtuins, including AMP-activated protein kinase (AMPK) and PGC-1α, known to be regulated by DR in mammals (Pirola and Frojdo 2008). Through these targets, resveratrol exerts numerous beneficial effects in mammals ranging from increased insulin sensitivity, reduced plasma glucose and triglyceride levels, and attenuated oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the objective of this study was to analyze the effect of different presentations of resveratrol on cell proliferation and epithelial thickness of the oral mucosa of Wistar rats 11,12 .…”
mentioning
confidence: 99%
“…For instance, resveratrol prevents the proliferation of cancer cells, reduces the risk of cardiovascular diseases, and displays antidiabetic properties (2,3,5,7,8,16,33,45,49,53,59,70). The exact mechanism of action of resveratrol remains unclear, but in vivo and in vitro studies have suggested that this compound somehow affects glucose metabolism (7,10,33,41,58,66) perhaps by inhibiting GLUT1 activity.…”
mentioning
confidence: 99%